Dopamine induces platelet production from megakaryocytes via oxidative stress-mediated signaling pathways. (3rd October 2018) - Chen, Shilei; Hu, Mengjia; Shen, Mingqiang; Xu, Yang; Wang, Cheng; Wang, Xinmiao; Li, Fengju; Zeng, Dongfeng; Chen, Fang; Zhao, Gaomei; Chen, Mo; Wang, Fengchao; et al.
Abstract: Dopamine (DA), a catecholamine neurotransmitter, is known to for its diverse roles on hematopoiesis, yet its function in thrombopoiesis remains poorly understood. This study shows that DA stimulation can directly induce platelet production from megakaryocytes (MKs) in the final stages of thrombopoiesis via a reactive oxygen species (ROS)-dependent pathway. The mechanism was suggested by the results that DA treatment could significantly elevate the ROS levels in MKs, and time-dependently activate oxidative stress-mediated signaling, including p38 mitogen-activated protein kinase, c-Jun NH2-terminal kinase, and caspase-3 signaling pathways, while the antioxidants N-acetylcysteine and L-glutathione could effectively inhibit the activation of these signaling pathways, as well as the ROS increase and platelet production triggered by DA. Therefore, our data revealed that the direct role and mechanism of DA in thrombopoiesis, which provides new insights into the function recognition of DA in hematopoiesis.